How I Learned the Language of Spicy Food - Parra, Judith Lupita (Fresh Ink: Essays From Boston College’s First-Year Writing Seminar, 2011)
The following narrative describes the journey taken to overcome primarily language as well as cultural and societal obstacles as a first generation Latin American youth. The piece particularly describes the cultural limitations faced because of language barriers.